PENGARUH KUALITAS PELAYANAN DAN TARIF TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PELANGGAN FAMILY FUN KARAOKE KELUARGA OUTLET SMG-03 SEMARANG - Zulfa, Nur Amalia; Lubis, Nawazirul; Ngatno, Ngatno (Jurnal Ilmu Administrasi Bisnis, 2014)
As the development of the economy, companies in the services sector has increased rapidly, especially in entertainment services. This is due to the entertainment services has become people needs to relieve their fatigue and boredom from daily activities. In serving the customers, Family Fun Karaoke Keluarga Outlet SMG-03 Semarang is one of the karaoke company growing in Semarang, but the number of visitors has decreased from year 2011 – 2013 is accompanied by an increasing number of incoming complaints.This study aimed to know the effect of service quality and rate on customer loyalty through customer satisfaction Family Fun Karaoke Keluarga Outlet SMG-03 Semarang. Type of research is used explanatory. The population in this study is the customer Family Fun Karaoke Keluarga Outlet SMG-03 Semarang, by using the theory of Cooper and Emory then taken 100 respondents to be sampled and the sampling technique used a combination of incidental sampling and purposive sampling. Metohods of data collection using questionnaires, interviews, and documentation. Measurement scale used a Likert scale. The data analysis used validity test, reliability test, correlation coefficient, analysis of simple and multiple linear regression, determinant coefficient, significance test (t test and F test) and path analysis.The study concluded that the quality of service and rate altogether (simultaneously) or individually affect the dependent variable of customer satisfaction and customer loyalty. Based on the results of path analysis, the direct effect of service quality on customer loyalty smaller than the indirect effect, whereas the direct effect of rate on customer loyalty greater than the indirect effect.Suggestion of this study is Family Fun Karaoke Keluarga Outlet SMG-03 Semarang should be able to improve the quality of its services such as equipment provide, uniforms provide a more polite to work for employee and increase the ability of employees to serve customers and determine the relevant rate in order to continue to survive in the midst of intense competition at this time.